Communication technologies for vehicles : 14th International Workshop, Nets4Cars/Nets4Trains/Nets4Aircraft 2019, Colmar, France, May 16-17, 2019, proceedings /: 14th International Workshop, Nets4Cars/Nets4Trains/Nets4Aircraft 2019, Colmar, France, May 16-17, 2019, proceedings. ([2019]) - Unknown
No abstract available